Black students in imperial Britain : the African Institute, Colwyn Bay, 1889-1911. - Burroughs, Robert (Liverpool University Press, 2022)
This book caters for the demand in new black histories by rediscovering several little-known Black people’s experiences in late-Victorian Britain. It centres on The African Institute of Colwyn Bay, or ‘Congo House’, at which almost 90 children and young adults from Africa and its diaspora were enrolled to train as missionaries between 1889 and 1911. Burroughs finds that, though their encounters in Britain were shaped by the racism and paternalism of the late-nineteenth-century civilising mission, the students were not simply the objects of British charity. They were also agents in a culture of evangelical humanitarianism. Some were fully absorbed in the civilising mission, becoming leading missionaries. Others adapted their experiences to new ends, participating in networks of pan-Africanism that questioned race prejudice and colonialism. In their negotiations of the challenges and opportunities at the heart of the empire, the students of Congo House reveal how the global currents of black history shaped the localised cultures of Victorian philanthropy. From racism to pan-Africanism, this study sheds new light on key issues in black British history.